Long-Term Follow-Up After Percutaneous Transluminal Coronary Angioplasty Was Not Performed Based on Intravascular Ultrasound Findings - Alexandre Abizaid; Gary S. Mintz; Roxana Mehran; Alexandre Abizaid; Alexandra J. Lansky; Augusto D. Pichard; Lowell F. Satler; Hongsheng Wu; Chrysoula Pappas; Kenneth M. Kent; Martin B. Leon (1999)
Background —Angiography is limited in determining the anatomic severity of coronary artery stenoses. Clinical decision-making in patients with symptoms and intermediate lesions remains challenging. Methods and Results —The current analysis included 300 patients (357 intermediate native artery lesions) in whom intervention was deferred based on intravascular ultrasound (IVUS) findings. Standard clinical, angiographic, and IVUS parameters were collected. Patients were followed for >1 year. Events occurred in 24 patients (8%). They included 2 cardiac deaths, 4 myocardial infarctions, and 18 target-lesion revascularizations (TLR; 12 percutaneous transluminal coronary angiographies and 6 coronary artery bypass grafts; only 3 TLRs occurred within 6 months after the IVUS study). All significant univariate clinical, angiographic, and IVUS parameters ( P <0.05) were tested in multivariate models. These included diabetes mellitus, IVUS lesion lumen area, maximum lumen diameter, minimum lumen diameter, plaque area, plaque burden, and area stenosis (AS). No angiographic measurement was significant at P <0.05. The only independent predictors of an event (death, myocardial infarction, or TLR) were IVUS minimum lumen area and AS. The only independent predictors of TLR were diabetes mellitus, IVUS minimum lumen area, and AS. In 248 lesions with a minimum lumen area ≥4.0 mm 2 , the event rate was only 4.4% and the TLR rate 2.8%. Conclusions —Long-term follow-up after IVUS-guided deferred interventions in patients with de novo intermediate native artery lesions showed a low event rate. In patients with a minimum lumen area ≥4.0 mm 2 , the event rate was especially low. IVUS imaging is an acceptable alternative to physiological assessment in these patients.